92.0k views
5 votes
Simplify the equation -2(p + 4)2 - 3 + 5p. What is the simplified expression in standard form? ASAP PLEASE!! ILL GIVE EXTRA POINTS FOR FIRST ANSWER!!

User Janie
by
6.4k points

1 Answer

2 votes

Answer: The required simplified expression in standard form is
-2p^2-11p-35.

Step-by-step explanation: We are given to simplify the following equation and write the simplified expression in standard form :


E=-2(p+4)^2-3+5p~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We will be using the following formula :


(a+b)^2=a^2+2ab+b^2.

The simplification of expression (i) is as follows :


E\\\\=-2(p+4)^2-3+5p\\\\=-2(p^2+8p+16)-3+5p\\\\=-2p^2-16p-32-3+5p\\\\=-2p^2-11p-35.

Thus, the required simplified expression in standard form is
-2p^2-11p-35.

User Manish Dash
by
6.5k points